N Narrative Review : Ekstrak Daun Bangkal (Nauclea subdita .Merr) Terhadap Paru-Paru Hewan Uji yang Terpapar Polusi Udara Akibat Kebakaran Hutan - Shofi Maulana; Muhammad Rifqi Dharmawan; Wanda Nisa Pratiwi; Iwan Yuwindry (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
Background: Forest fires occur almost every year in Indonesia, especially during the extreme dry season. Forest fires have been anticipated in advance, but fires still occur. The haze from forest fires causes disturbances that cause health problems in the community, especially respiratory problems as a result. Objective: to determine the efficacy of bangkal leaf extract (Nauclea subdita .Merr) as a treatment for Acute Respiratory Tract Infection (ARI), so that it can support the government in reducing the incidence of Acute Respiratory Tract Infection (ARI) due to forest fires. Methods: used in writing this article is Narrative Review, which is a literature search both nationally and internationally traced through indexed journal sites such as PubMed and Google Scholar. Results: obtained after reviewing the article shows that bangkal leaf extract (Nauclea subdita .Merr) can be efficacious as a treatment for Acute Respiratory Infections (ARI) because it contains flavonoids that can be used as antioxidants. Conclusion:  from the review of articles conducted by researchers about forest fires that can cause problems in the respiratory tract can be overcome with bangkal leaf extract (Nauclea subdita .Merr) as a natural treatment to treat Acute Respiratory Tract Infection (ARI).